Tissue Engineering Considerations in Dental Pulp Regeneration - Nosrat, Ali; Kim, Jong Ryul; Verma, Prashant; Chand, Priya S. (Iranian Endodontic Journal, 2013)
Regenerative endodontic procedure is introduced as a biologically based treatment for immature teeth with pulp necrosis. Successful clinical and radiographic outcomes following regenerative procedures have been reported in landmark case reports. Retrospective studies have shown that this conservative treatment allows for continued root development and increases success and survival rate of the treated teeth compared to other treatment options. Although the goal of treatment is regeneration of a functional pulp tissue, histological analyses show a different outcome. Developing predictable protocols would require the use of key elements for tissue engineering: stem cells, bioactive scaffolds, and growth factors. In this study we will review the evidence based steps and outcomes of regenerative endodontics.